Incidence of carbapenem resistant nonfermenting gram negative bacilli from patients with respiratory tract infections among intensive care units - Devi, P. Vasundhara; Reddy, P. Sreenivasulu; John, Maria Sindhura (International Journal of Research in Medical Sciences, 2017)
Background: Non fermenting gram negative bacilli that were considered to be contaminants in the past have now emerged as important healthcare- associated pathogens. Pseudomonas aeruginosa and Acinetobacter species are now known to be the common nosocomial pathogens. Carbapenems are one of the essential antibiotics in the armamentarium against, serious nosocomial infections. Development of resistance against these is a cause of concern. Misuse and inappropriate duration of antibiotic therapy helps in development of resistance. Methods: A total of 200 endo tracheal aspirates and sputum samples were collected from patients of all age groups with clinical evidence of lower respiratory tract infection from Medical, surgical, pediatric ICUS. Non fermenting gram negative bacilli isolated and identified according to CLSI guidelines and antibiotic sensitivity test was performed by Kirby Bauer disc diffusion method. Results: Out of 200 samples 50 Acinetobacter spp. and 38 Pseudomonas aeruginosa were isolated. Among 38 Pseudomonas isolates (42%) 16 were resistant to imipenem and 11 (29%) were resistant to meropenem. Among 50 Acinetobacter isolates 14 (28%) were resistant to imipenem and 12 (24%) were resistant to meropenem. Conclusions: Our study documents an increase in the carbapenem resistance. Reduction in antimicrobial resistance in the ICUS has been a goal for all ICUS as it improves outcome and cost of patient care. Carbapenem must be used judiciously to prevent further resistance or else this would erode the strength of life saving antibiotics.